Análise dinâmica de torres metálicas treliçadas estaiadas e autoportantes de linhas de transmissão submetidas à ruptura de cabos - Just, Lucas de Oliveira (2021)
The reliability of the electric power transmission systems is due, in addition to other factors, to the structural stability of the supports that hold the conductive cables and lightning rods along the transmission lines. The support structures, usually latticed metal towers, in addition to the usual demands on other structures, such as self-weight and wind, are subject to a specific request, caused by the rupture of one or more cables. This request is of a dynamic nature and for a precise analysis of this event, the method of direct integration with central finite differences is used. In this work, models of transmission lines with 5 towers, self-supporting and cable-stayed, are analyzed in order to simulate the interaction between supports and cables. This procedure aims to investigate the influence of dynamic analysis on the design and structural safety of the towers. The results obtained with the direct integration method are compared with those obtained in a static analysis, usual in current projects. The difference between the results is evaluated from the perspective of structural safety and the influence on the design of the towers. The differences between the approaches and between the behaviors of the two types of tower show that the static analysis may not be sufficient for a good structural representation of the cable rupture phenom.